2010
DOI: 10.1371/journal.pone.0008626
|View full text |Cite
|
Sign up to set email alerts
|

Control of Alzheimer's Amyloid Beta Toxicity by the High Molecular Weight Immunophilin FKBP52 and Copper Homeostasis in Drosophila

Abstract: FK506 binding proteins (FKBPs), also called immunophilins, are prolyl-isomerases (PPIases) that participate in a wide variety of cellular functions including hormone signaling and protein folding. Recent studies indicate that proteins that contain PPIase activity can also alter the processing of Alzheimer's Amyloid Precursor Protein (APP). Originally identified in hematopoietic cells, FKBP52 is much more abundantly expressed in neurons, including the hippocampus, frontal cortex, and basal ganglia. Given the fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
59
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(64 citation statements)
references
References 42 publications
5
59
0
Order By: Relevance
“…This effect is dose-dependent: increasing the amount of Gal4 produced per cell by adding another motoneuron-specific driver OK371-Gal4 to D42-Gal4 to express the Aβ42 peptide further reduced the median life span to 10 days (p = 0.0028, Log-rank test) and the maximal survival to 14 days ( Figure 1B). Cumulatively, these findings suggest that the major effect of Aβ42 on the life span observed previously [15,16] by the pan-neuronal Aβ42 expression takes place in glutamatergic neurons.…”
Section: Resultssupporting
confidence: 52%
See 2 more Smart Citations
“…This effect is dose-dependent: increasing the amount of Gal4 produced per cell by adding another motoneuron-specific driver OK371-Gal4 to D42-Gal4 to express the Aβ42 peptide further reduced the median life span to 10 days (p = 0.0028, Log-rank test) and the maximal survival to 14 days ( Figure 1B). Cumulatively, these findings suggest that the major effect of Aβ42 on the life span observed previously [15,16] by the pan-neuronal Aβ42 expression takes place in glutamatergic neurons.…”
Section: Resultssupporting
confidence: 52%
“…The genetic model organism Drosophila melanogaster has also been used to study the mechanisms of AD [14]. In this model, several possibilities to mimic AD are available; amongst others the neuronal expression of human Aβ42 peptide [15,16]. These flies recapitulate several aspects of AD observed in patients: they show learning deficits, reduced locomotion, shorter life span and neurodegeneration and amyloid deposition in the brain [15].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cu 2ϩ ions are found concentrated within senile plaques of AD patients directly bound to A␤ (3)(4)(5). Recent in vivo studies using a Drosophila model of AD have shown that impaired copper homeostasis enhances the toxic effects of A␤ (6). Furthermore, copper in a cholesterol high diet induces amyloid plaques and learning deficits in a rabbit model of AD (7).…”
Section: Alzheimer Disease (Ad)mentioning
confidence: 99%
“…Furthermore, FKBP52 is upregulated after injury in regenerating neurons and Alzheimer's patients have a lower expression of FKBP52 in the temporal lobe and hippocampus 131 . FKBP52 is involved in the regulation of intracellular copper and this may cause FKBP52 to have an effect on Aβ levels [144][145][146] . Furthermore, Conejero-Goldberg and colleagues demonstrated that FKBPL was one of the key genes differentially expressed in the brain tissue, where it appeared to act in a protective role, in young individuals at high risk of Alzheimers disease preselected by the APO4 signature 147 .…”
Section: The Role Of Ppiases In Neurodegenerationmentioning
confidence: 99%